Cardiovascular risk factors and clinical outcomes of patients hospitalized with COVID-19 pneumonia in Somalia - Ahmed, Mohammed A.M.; Mohamud Hussein, Ahmed; Ahmed Moalim Abdullahi, Aweis; Yusuf Ahmed, Abdirizak; Hussain, Hamdi M.A.; Mohamed Ali, Abdiaziz; Abdinur Barre, Abdulqadir; Mohamud Yusuf, Farhia; Olum, Ronald; Goitom Sereke, Senai; Ahmed Elfadul, Maisa; Colebunders, Robert; et al. (Therapeutic Advances in Infectious Disease, 2022)
Coronavirus disease-2019 (COVID-19) is a potentially life-threatening illness with no established treatment. Cardiovascular risk factors (CRFs) exacerbate COVID-19 morbidity and mortality. Objective: To determine the prevalence of CRF and clinical outcomes of patients hospitalized with COVID-19 in a tertiary hospital in Somalia. Methods: We reviewed the medical records of patients aged 18 years or older with a real-time polymerase chain reaction (RT-PCR)–confirmed COVID-19 hospitalized at the De Martino Hospital in Mogadishu, Somalia, between March and July 2020. Results: We enrolled 230 participants; 159 (69.1%) males, median age was 56 (41–66) years. In-hospital mortality was 19.6% (n = 45); 77.8% in the intensive care unit (ICU) compared with 22.2%, in the general wards (p < 0.001). Age ⩾ 40 years [odds ratio (OR): 3.6, 95% confidence interval (CI): 1.2–10.6, p = 0.020], chronic heart disease (OR: 9.3, 95% CI: 2.2–38.9, p = 0.002), and diabetes mellitus (OR: 3.2, 95% CI: 1.6–6.2, p < 0.001) were associated with increased odds of mortality. Forty-three (18.7%) participants required ICU admission. Age ⩾ 40 years (OR: 7.5, 95% CI: 1.7–32.1, p = 0.007), diabetes mellitus (OR: 3.2, 95% CI: 1.6–6.3, p < 0.001), and hypertension (OR: 2.5, 95% CI: 1.2–5.2, p = 0.014) were associated with ICU admission. For every additional CRF, the odds of admission into the ICU increased threefold (OR: 2.7, 95% CI: 1.2–5.2, p < 0.001), while the odds of dying increased twofold (OR: 2.1, 95% CI: 1.3–3.2, p < 0.001). Conclusions: We report a very high prevalence of CRF among patients hospitalized with COVID-19 in Somalia. Mortality rates were unacceptably high, particularly among those with advanced age, underlying chronic heart disease, and diabetes.
Keywords: Cardiovascular disease; Clinical outcomes; COVID-19; Diabetes; Mortality; Risk factors